Thermogeological function of burrow system in Phrynocephalus przewalskii. (October 2021) - Chen, Xubin; Li, Tianyao; Chen, Chen; Chang, Yinyi; Li, Pengtao; Han, Yunchun; Zhao, Wei
Abstract: Burrow system has been proven to be an effective strategy to avoid the interference of adverse circumstances on nesting animals inhabiting the unsuitable environment. To verify the ecological function of burrows in Phrynocephalus przewalskii, 20 sets of thermal characteristics including bottom temperature of real and manmade burrow, and sand surface temperature at burrow entrance were recorded every 2 h from 8:00 to 20:00 during two sunny days in mid-July, the hottest period in Minqin, China. During daytime, the sand surface experienced extremely high and fluctuating temperature (43.6 ± 12.91 °C average, CV = 0.303 ± 0.226), followed by the bottom temperature in manmade burrow (34.7 ± 7.76 °C, CV = 0.221 ± 0.018), and a lower fluctuating range for bottom temperature in real burrow (29.0 ± 2.91 °C, CV = 0.089 ± 0.026). During the entire daytime period, the real burrow was thermally available for P. przewalskii under the standard Tb50% or Tb80%, where the livable time decreased to 41.4% and 44.4% of daytime period for sand surface, and 62.3% and 80.1% for manmade burrow, respectively. We inferred that the ecological significance of burrow system in buffering the temperature fluctuation is attributed to its unique structure, which is absent in the manmade burrow. This feature of the burrow system not only mitigated the diurnal temperature surge, but also prolonged its thermally suitable time for P. przewalskii under the harsh desert climate. Highlights: Burrow buffers temperature fluctuation and defers adverse circumstance in desert. Buffering effect of burrow system prolongs thermally suitable time for P. Przewalskii . The ecological function of burrow system relies on its unique structure.